EFFECTS OF ASTHMA (Euphorbia hirta) AND BLACKJACK (Biden pilosa) WEEDS EXTRACTS ON Meloidogyne incognita EGG HATCHABILITY. - Idris K.; Adamu M. Y.; Garba A. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study investigated the nematicidal potential of aqueous extracts from two common weeds, Euphorbia hirta (Asthma plant) and Bidens pilosa (Blackjack), on the egg hatchability of Meloidogyne incognita. The study is guided by two Objectives; to assess the impact of different concentrations of aqueous extracts of Asthma and blackjack weeds on M. incognita egg hatchability and to compare the efficacy of asthma and blackjack weeds extracts on M. incognita egg hatchability. The experiment was laid in a Randomized Complete Block Design (RCBD) with nine treatments and three replications. Treatments included crude extracts (T1 & T5) of E. hirta and B. pilosa, and (T2, T3, T4 ,….. T8) and their subsequent dilutions at 5 ml, 10 ml, and 15 ml, along with a control/untreated group (T9). Results demonstrated significant differences in egg hatchability among treatments. B. pilosa crude extract (T5) exhibited the most potent effect, recording the lowest egg hatchability at 6.00%. Followed by its diluted forms 16%, 20%, and 23% for the 5 ml, 10 ml, and 15 ml dilutions, respectively. Conversely, the crude E. hirta extract resulted in 53% egg hatchability, and its dilutions showed increasing hatchability with increasing dilution, recording 68%, 69%, and 73% for the 5 ml, 10 ml, and 15 ml treatments, respectively. While the control group exhibited an 89% egg hatch. These findings revealed that Bidens pilosa, particularly its crude extract, possesses strong nematicidal properties against M. incognita egg hatch. Further research is warranted to isolate and characterize more of the active compounds responsible for this activity and to evaluate their efficacy under field conditions as potential sustainable alternatives for nematode management.